2011
DOI: 10.1074/jbc.m110.198101
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Stability of the N-domain Underlies Distinct Intracellular Properties of the E1064A and H1069Q Mutants of Copper-transporting ATPase ATP7B

Abstract: Wilson disease (WD) is a disorder of copper metabolism caused by mutations in the Cu-transporting ATPase ATP7B. WD is characterized by significant phenotypic variability, the molecular basis of which is poorly understood. The E1064A mutation in the N-domain of ATP7B was previously shown to disrupt ATP binding. We have now determined, by NMR, the structure of the N-domain containing this mutation and compared properties of E1064A and H1069Q, another mutant with impaired ATP binding. The E1064A mutation does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…This process may occur, since the third and fourth Cu-binding domains in the Nterminal portion of ATP7B have been shown to aggregate in vitro (Banci et al, 2008). Given that the H1069Q mutation might affect the strength of interaction between NBD and N-terminal domains of ATP7B (Dmitriev et al, 2011), the third and fourth Cu-binding domains in the N-terminal portion of the mutant ATP7B molecules could potentially acquire more freedom to oligomerise and generate ATP7B-H1069Q aggregates. CRYAB may counteract these aggregation events by holding the Nterminal tails of ATP7B-H1069Q molecules from oligomerization and in this way may help the mutant be exported from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…This process may occur, since the third and fourth Cu-binding domains in the Nterminal portion of ATP7B have been shown to aggregate in vitro (Banci et al, 2008). Given that the H1069Q mutation might affect the strength of interaction between NBD and N-terminal domains of ATP7B (Dmitriev et al, 2011), the third and fourth Cu-binding domains in the N-terminal portion of the mutant ATP7B molecules could potentially acquire more freedom to oligomerise and generate ATP7B-H1069Q aggregates. CRYAB may counteract these aggregation events by holding the Nterminal tails of ATP7B-H1069Q molecules from oligomerization and in this way may help the mutant be exported from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…Two well-characterized trafficking signals encoded within the primary sequences of both copper-ATPases have been identified: (i) F 37 -E 45 in ATP7B, which is required for retention of ATP7B in the TGN (−Cu) and targeting to the apical region in polarized hepatic cells (+Cu, anterograde trafficking) (11); and (ii) di-and trileucines in ATP7A and ATP7B's C-termini, which are needed for retrograde trafficking to the TGN (−Cu) (12,41,42). Trafficking also requires MBD5 or MBD6 (10), the C terminus (12), nucleotide binding-domain stability (43), and ATPase-dependent coppertransport activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…This evidence is in agreement with some previous studies, which demonstrated that ATP7B mutation in transmembrane and ATP-binding domains (block 1) have a strong impact on protein function. [33][34][35] It is noteworthy that rs1061472 and rs732774, strongly associated with AD in our study population, are located in transduction and transmembrane domains.…”
Section: Atp7b In Alzheimer Diseasementioning
confidence: 99%